2016
DOI: 10.1021/acs.biomac.6b00350
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Responsive Polymersomes for Drug Delivery to Hypoxic Pancreatic Cancer Cells

Abstract: Hypoxia in tumors contributes to overall tumor progression by assisting in epithelial-to-mesenchymal transition, angiogenesis, and metastasis of cancer. In this study, we have synthesized a hypoxia-responsive, diblock copolymer poly(lactic acid)–azobenzene–poly(ethylene glycol), which self-assembles to form polymersomes in an aqueous medium. The polymersomes did not release any encapsulated contents for 50 min under normoxic conditions. However, under hypoxia, 90% of the encapsulated dye was released in 50 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
116
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 27 publications
1
116
0
Order By: Relevance
“…[27][28][29] As the azobenzene units were reduced to the corresponding anilines by azoreductase under the hypoxic condition, the polymeric assemblies formed by azobenzene-containing polymers successfully released the encapsulated drugs or siRNA to hypoxic cancer cells. 30,31 It was found that doxorubicin (DOX)-loaded nanoparticles of nitroimidazolemodified polymers selectively accumulated at the hypoxic tumor tissues and exhibited high antitumor activity in vivo. 32 Under hypoxic conditions, p-nitrobenzyl alcohol derivatives (NADs) are highly labile and readily degraded by a 1,6-elimination reaction in the presence of NTR with nicotinamide adenine dinucleotide as an electron donor.…”
mentioning
confidence: 99%
“…[27][28][29] As the azobenzene units were reduced to the corresponding anilines by azoreductase under the hypoxic condition, the polymeric assemblies formed by azobenzene-containing polymers successfully released the encapsulated drugs or siRNA to hypoxic cancer cells. 30,31 It was found that doxorubicin (DOX)-loaded nanoparticles of nitroimidazolemodified polymers selectively accumulated at the hypoxic tumor tissues and exhibited high antitumor activity in vivo. 32 Under hypoxic conditions, p-nitrobenzyl alcohol derivatives (NADs) are highly labile and readily degraded by a 1,6-elimination reaction in the presence of NTR with nicotinamide adenine dinucleotide as an electron donor.…”
mentioning
confidence: 99%
“…Our hypothesis was based on the fact that such programmed disintegration of larger nanoparticles will provide with deeper penetration of drug‐transporting nanocarriers through the dense desmoplastic microenvironment of pancreatic cancer. We selected pH as the stimulus to trigger such controlled destabilization because for PDAC and any other form of solid tumors, pH decreases sharply in conjunction with low O 2 tension as the distance increases from blood vessels to tumor tissues . In addition, smaller nanoparticles are required to penetrate deep‐seated tumor cells and cancer‐like stem cells, many of which are difficult to reach with larger nanoparticles due to altered microvasculature present in solid tumors.…”
Section: Resultsmentioning
confidence: 99%
“…The hypoxia‐responsive release of aTGFβRII was evaluated according to the method previously described . Briefly, 0.35 mL A azo @CMSN aqueous solution (5 mg mL −1 ) were placed in Eppendorf tubes followed by adding 50 µL PBS (0.1 m ), 30 µL rat liver microsomes, and 70 µL NADPH (2 × 10 −3 m ).…”
Section: Methodsmentioning
confidence: 99%